Chapter 6 Biology and Ecology of the Globally Significant Kelp Ecklonia radiata - Wernberg, Thomas (Oceanography and Marine Biology : An Annual Review, 2019)
Ecklonia radiata is one of the most widespread kelps globally, dominating temperate reefs throughout much of Australasia and southeastern Africa. Throughout much of its range, it is the only laminarian kelp and hence plays a key role in facilitating biodiversity and driving food webs, and it underpins immense ecological and socioeconomic values. This review synthesises the growing literature on E. radiata from its phylogeny and distribution through to its biology, ecology and recent changes. It provides an assessment of the state of knowledge and identifies gaps in our understanding of this important species. Despite being tolerant of a wide range of abiotic conditions, recent environmental change has caused direct and indirect loss of E. radiata forests, with extensive areas transitioning to turf and urchin barrens. Ongoing climate change may require application of multifaceted and novel strategies to increase its resistance and resilience to future conditions. By integrating variation across space, time and environmental change, this review provides a description of the current status and possible future trajectories of E. radiata forests.